Total factor productivity growth in developing economies: a study of selected industries in India - Pradhan, Gopinath; Barik, Kaustuva (1999)
Management of total factor productivity in developing economies remains, by and large, an unresolved problem despite industrialisation through efficient resource-use becoming a major objective of the economic reform programme. The present study attempts to open a solution channel by considering TFPG as a result of interaction between economies of scale and technical change. Thus, it seeks to lay emphasis on proper management of scale economies and technical change for producing a desired TFPG. For that purpose, estimation of TFPG is carried out with the help of translog cost function, which gives information on these two components simultaneously. The empirical findings of the exercise on data of aggregate manufacturing sector and eight selected industries of India indicate that both scale economies and technical change have registered a declining trend in recent years producing in the process a declining TFPG. There exists, therefore, a good case for prescribing policy measures that lead to better exploitation of economies of scale and technical change in India. - Reproduced
Keywords: India - Industries; Industrial development